O reatamento das relações sino-americanas (1969-1972): um estudo tripartido da maximização do poder rumo à hegemonia Norte-americana na Àsia - Andrade, George Bronzeado de (2014)
The end of the 60s and early 70s is marked by the resumption of Sino-US relations under the sign of detente. At this moment in history, the United States Richard Nixon and Communist China of Mao Zedong resume interrupted a relationship for more than twenty years, marked by failure dating back to the victory of the Communist Revolution of Mao Zedong in 1949. Their reunion of two nations, who advocated socio-economic systems and differing ideologies, outside this period grassada the realistic pragmatism policies of Washington and Beijing. It's about this phenomenon that in many ways "shocked" the world, which seeks to undertake a multidimensional understanding of Sino-American resumption under the tripartite perspective of the study of history, analysis of official documents from the U. S. State Department and reading theory to explain the phenomenon of rapprochement, with emphasis on the approach of offensive realism Mearsheimer, who intuits to an American company in the Asian region towards maximizing power with the purpose of seeking regional hegemony.